Anticipation of badminton serves during naturalistic match-play: a case for the post-performance analysis of perceptual-cognitive skills - Roberts, J. W.; Keen, B.; Kawycz, S. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: It has been frequently evidenced that skilled sport performers distinguish themselves from less-skilled based on key temporally constrained perceptual cues in order to anticipate future events. However, the evidence to-date has arguably failed to reflect the true nature of perceptual-cognitive skill in sport, and thus negated any robust suggestions for the assessment and training of athletes. The present study attempts to address this issue by observing measures of anticipation within purely naturalistic match-play. METHODS: A series of skilled (N.=8) and less-skilled (N.=8) badminton players undertook regular match-play while an equal number of digital recordings were made of their return-of-serve (N.=10). Frame-by-frame analyses were conducted to indicate the moment of initiation and accuracy of initial response selection. RESULTS: Inter-observer agreement for time (r=0.70, P<0.00) and accuracy (90.63%) measures were robust. Performance differences between the groups were stark including significant differences for time (median: skilled 184 ms; less-skilled 322 ms) and accuracy (median: skilled 9; less-skilled 6) (P<0.00). CONCLUSIONS: Influence of skill level corresponds with empirically derived suggestions of skilled athletes accessing domain-specific knowledge for the anticipation of future events. Thus, the naturalistic performance setting offers a viable alternative for further examination, while additionally incorporating the invariant features and contextual information that underlie sport performance.